Ultrafast FRET to Study Spontaneous Micelle‐to‐Vesicle Transitions in an Aqueous Mixed Surface‐Active Ionic‐Liquid System1. Issue 16 (5th September 2014) - Mandal, Sarthak; Kuchlyan, Jagannath; Banik, Debasis; Ghosh, Surajit; Banerjee, Chiranjib; Khorwal, Vijaykant; Sarkar, Nilmoni
Abstract The spontaneous micelle‐to‐vesicle transition in an aqueous mixture of two surface‐active ionic liquids (SAILs), namely, 1‐butyl‐3‐methylimidazolium n‐octylsulfate ([C4mim][C8SO4]) and 1‐dodecyl‐3‐methylimidazoium chloride ([C12mim]Cl) is described. In addition to detailed structural characterization obtained by using dynamic light scattering, transmission electron microscopy (TEM), and cryogenic TEM techniques, ultrafast fluorescence resonance energy transfer (FRET) from coumarin 153 (C153) as a donor (D) to rhodamine 6G (R6G) as an acceptor (A) is also used to study micelle–vesicle transitions in the present system. Structural transitions of SAIL micelles ([C4mim][C8SO4] or [C12mim]Cl micelles) to mixed SAIL vesicles resulted in significantly increased D–A distances, and therefore, increased timescale of FRET. In [C4mim][C8SO4] micelles, FRET between C153 and R6G occurs on an ultrafast timescale of 3.3 ps, which corresponds to a D–A distance of about 15 Å. As [C4mim][C8SO4] micelles are transformed into mixed micelles upon the addition of a 0.25 molar fraction of [C12mim]Cl, the timescale of FRET increases to 300 ps, which suggests an increase in the D–A distance to 31 Å. At a 0.5 molar fraction of [C12mim]Cl, unilamellar vesicles are formed in which FRET occurs on multiple timescales of about 250 and 2100 ps, which correspond to D–A distances of 33 and 47 Å. Although in micelles and mixed micelles the obtained D–A distances are well correlated with their radius, in vesicles the obtained D–A distance is within the range of the bilayer thickness.